2005
DOI: 10.1128/aem.71.7.4137-4139.2005
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Botulinum Toxin-Producing Clostridia in Soils of Argentina

Abstract: We studied the presence of botulinum toxin-producing clostridia in 2,009 soil samples from five geographical regions of Argentina. The prevalence was 23.5%, and the distribution was not homogeneous among the regions. We observed a great multiplicity of serological types and a higher prevalence in nonvirgin soils than in virgin soils.The geographical distribution of botulinum toxin-producing clostridia (BTPC) (7) has been extensively studied in Europe, Asia, and North America (1,2,4,5,8,9,10,11,12,13,15,16,18,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 20 publications
1
21
0
1
Order By: Relevance
“…For example, all 4 cases reported in Norway showed a history of honey exposure and were type A, although C botulinum type A has not been found in soil in Norway 111 or in honey produced in Norway. 96 The honey consumed by 1 of the Norwegian case subjects originated in Argentina, 60 where C botulinum type A has commonly been found in soil 109 and in locally produced honey. C botulinum spores have also been found in honeys produced in Asia, Europe, and North America.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, all 4 cases reported in Norway showed a history of honey exposure and were type A, although C botulinum type A has not been found in soil in Norway 111 or in honey produced in Norway. 96 The honey consumed by 1 of the Norwegian case subjects originated in Argentina, 60 where C botulinum type A has commonly been found in soil 109 and in locally produced honey. C botulinum spores have also been found in honeys produced in Asia, Europe, and North America.…”
Section: Discussionmentioning
confidence: 99%
“…106 As occurs in the United States, 107 in most countries the toxin types of C botulinum that caused cases of infant botulism reflected the geographical distribution of toxin types of C botulinum spores found in that country's environment. [108][109][110][111][112][113][114][115][116] However, some cases with a history of honey exposure were found to be affected by C botulinum toxin types that are not native to their environment. For example, all 4 cases reported in Norway showed a history of honey exposure and were type A, although C botulinum type A has not been found in soil in Norway 111 or in honey produced in Norway.…”
Section: Discussionmentioning
confidence: 99%
“…Among 68 outbreaks of serotype-confirmed food-borne botulism in Argentina between 1922 and 2007, type F was isolated in two outbreaks, and type Af was isolated in one outbreak. In addition, Lúquez et al (26) reported isolation of type F and Af strains from Argentine soils.…”
mentioning
confidence: 99%
“…botulinum type Af was first isolated from a soil sample in Mendoza, Argentina (14). In a subsequent study of soil samples from that country, C. botulinum type Af was identified in 17 of 470 (3.6%) samples (15). In addition, type Af was reported as the cause of a case of food-borne botulism in Mendoza, Argentina, in 1982 (16).…”
Section: ) (4 5)mentioning
confidence: 99%